1980
DOI: 10.1073/pnas.77.9.5552
|View full text |Cite
|
Sign up to set email alerts
|

Release of immunoreactive somatostatin from hypothalamic cells in culture: inhibition by gamma-aminobutyric acid.

Abstract: Primary cultures of dispersed hypothalamic cells were prepared from embryonic rats to study the release of immunoreactive somatostatin. The immunoreactive somatostatin content of these cultures increased during the first 2 weeks after plating and was readily measurable for several weeks thereafter; this material was characterized by gel permeation and reverse-phase chromatography. Depolarization of the cells with 60 mM K+ or with veratridine resulted in a calcium-dependent release of immunoreactive somatostati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 31 publications
4
33
0
Order By: Relevance
“…For elucidation of the biosynthetic relationships between 15,000-mol-wt SLI, S-28, and S-14, the hypothalamus offers the distinct advantage of containing substantial quantities of all three molecular forms as opposed to tissues such as the pancreas, which have been studied previously (5). Primary cultures of dispersed hypothalamic and cerebrocortical cells derived from fetal rat brain and containing SLI have recently been described from two laboratories (25,26). the cultured neonatal hypothalamic cells in the present study are comparable to those reported for the two fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For elucidation of the biosynthetic relationships between 15,000-mol-wt SLI, S-28, and S-14, the hypothalamus offers the distinct advantage of containing substantial quantities of all three molecular forms as opposed to tissues such as the pancreas, which have been studied previously (5). Primary cultures of dispersed hypothalamic and cerebrocortical cells derived from fetal rat brain and containing SLI have recently been described from two laboratories (25,26). the cultured neonatal hypothalamic cells in the present study are comparable to those reported for the two fetal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…158,159 Baclofen, a GABA B receptor agonist, stimulates GH secretion in healthy individuals, [160][161][162] and is considered to be an in vivo index of human hypothalamic GABA B receptor function. The GH response to baclofen has been found to be significantly lower in depressed patients 163,164 and significantly higher in manic patients than healthy subjects.…”
Section: 157mentioning
confidence: 99%
“…Subsequently, it has become evident that this peptide has a widespread distribution throughout the central, peripheral, and gastrointestinal nervous systems and the endocrine pancreas (2-6). Its role as a neurotransmitter in the central nervous system is supported by its presence in neuronal cell bodies and terminals in several regions (2,(7)(8)(9), its calcium-dependent release upon depolarization (10)(11)(12), and its ability to affect neuronal activity (13)(14)(15)(16)(17)(18)(19)(20). Subsequent chemical (5,6) and cytochemical (8,21) studies revealed that the cellular localization and the major biological actions of somatostatin are shared with a larger 28 amino acid form, of which the original somatostatin is the C-terminal tetradecapeptide (SS-14).…”
mentioning
confidence: 99%